BIOGRAPHY STUDY OF IDEAS OF SULTAN SULAIMAN (HEAD OF SERDANG SULTANATE V, 1880-1946) FOR ARTS (MUSIC) DEVELOPMENT IN SERDANG SULTANATE - Ifwa Nulhakim (Grenek: Jurnal Seni Musik, 2019)
This work presents an academic study of the musical biography of Sultan Sulaiman, the fifth head of Serdang Sultanate, North Sumatera, Indonesia, in period 1880-1946. The discussion will lead to discussing the impact of his musical thinking and activity for the arts (espesially on music) atmosphere in the Sultanate. It will be concern on anything he did for music development in Serdang Sultanate during his commander and the impact after his period.  In addition, this study will be presents in brief the correlation between Sultan’s music activity and  the political situation at that time. The method used in this research is the qualitative method with biography approach. The data and information will be obtained in two ways, primary and secondary. The data and information which include in primary method will come from interview which use the in-depth interview approach. While the secondary method involves data collection via secondary sources which will come from books, journals, articles, conference papers, published dissertations, audio or video recording, diary book, music hand-sheet and other sources which support the research topic.This study find that Sultan Sulaiman is the root of arts development in the Serdang Sultanate. This is evidenced by the many art activities he conserve and develop such as Nobat Diraja, Mak Yong, Brass Band, and Serampang Dua Belas dance. The activities he did on the past give many impact for art development in Serdang in nowadays. It also stated that the art’s idea of Sultan Sulaiman is a part of political strategy.